INVENTARISASI ALAT TANGKAP BERDASARKAN KATEGORI STATUS PENANGKAPAN IKAN YANG BERTANGGUNGJAWAB DI PERAIRAN TANAH LAUT - Rusmilyansari Rusmilyansari (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Fisheries development programs in an effort to improve the well-being should also reflect an effort to preserve its resources . This study aims to determine the status of fishing gear base on category Responsibility Fisheries. The study was conducted in Tanah Laut district. Research carried out by the method of observation and interview based. The data were analyzed descriptively. The results showed that the fishing gears base on responsible category are longline and set gillnet; less responsible category are encircling gillnet, drift gillnet, trammel net, purse seine and beach siene. While the not responsible categories are Skimming net and Mini Trawl. Policy commendations can be done by controlling the amount of fishing gear, fishing area closures and strengthening stakeholder awareness. Thus the management of fishery resources in the context of sustainable development can be implemented.